Water mites from Mount Kinabalu and the Crocker Range, Borneo, Malaysia (Acari: Hydrachnidia), with the description of 34 new species - Smit, Harry; Pešić, Vladimir (Zootaxa, 2014)
Descriptions are presented of new species of water mites from two mountains in the Malaysian part of Borneo. A new subgenus of the genus Javalbia (Hygrobatidae), i.e. Megapes n. subgen., and 34 new species are described: Limnocharidae: Limnochares (Limnochares) spinosa n. sp.; Oxidae: Oxus (Oxus) fuscus n. sp.; Hydryphantidae: Protzia borneoensis n. sp.; Sperchontidae: Sperchon kinabaluensis n. sp., Sperchonopsis orientalis n. sp.; Hygrobatidae: Hygrobates (Hygrobates) acutipalpis n. sp., H. (Hygrobates) hamatoides n. sp., H. (Hygrobates) striatus n. sp., Atractides (Atractides) neospatiosus n. sp., A. (Atractides) sabahensis n. sp., A. (Atractides) crockerensis n. sp., A. (Atractides) curtisetus n. sp., A.(Tympanomegapus) borneoensis n. sp.; Frontipodopsidae: Frontipodopsis suturalis n. sp.; Aturidae: Javalbia (Javalbia) montana n. sp., J. (Javalbia) solitaria n. sp., J. (Javalbiopsis) borneoensis n. sp., J. (Javalbiopsis) kinabaluensis n. sp., J. (Javalbiopsis) magniseta n. sp., J. (Javalbiopsis) reticulata n. sp., J. (Megapes) uncinata n. sp., Albaxona mahuaensis n. sp., Axonopsis (Axonopsis) longigenitalis n. sp., A. (Axonopsis) rugosa n. sp., A. (Paraxonopsis) truncata n. sp., A. (Brachypodopsis) latipalpis n. sp., A. (Vicinaxonopsis) caeca n. sp., Erebaxonopsis kipungitensis n. sp., Ljania inconspicua n. sp., L. obliterata n. sp., Albia (Albiella) crocker n. sp., Aturus borneoensis n. sp.; Athienemanniidae: Africasia acuticoxalis n. sp.; Arrenuridae: Thoracophoracarus uniacetabulatus n. sp. A key is presented for the Javalbia species of Borneo. New records are given for 10 further species. In the course of revisional work, lectotypes are designated for the following species: Atractides cognatus (K. Viets) and A. propatulus (K. Viets).